Immune complexes and apoptosis in B-cell chronic lymphocytic leukemia - Gamberale, Romina (2002)
The progressive accumulation of B-cell chronic lymphocytic leukemia (B-CLL) cells in vivo is attributed to resistance to apoptosis, although this can be modulated in vitro by a variety of cellular and humoral factors (cell-cell, cell-matrix interactions, cytokines). We have previously reported that IgG immune complexes (IC) delay B-CLL cell apoptosis through a paracrine mechanism, which depends on monocytes and NK cells. On the other hand, despite the fact that IC effectively bind to type II FcγRs expressed on B-CLL cells, they are unable to deliver transmembrane signals. We speculate that this lack of responsiveness of resting B-CLL cells to IC could be overcome by activation. The analysis of this possibility would be relevant since the presence of circulating IC is a common feature in B-CLL patients.